That's life [compact disc] - Nelson, Willie, 1933- (Legacy, 2021)
Honoring the enduring inspiration of Frank Sinatra is Willie Nelson's second album of classics made famous by the Chairman of the Board. Nelson delivers 11 new studio performances, coming alive in a musical landscape animated by lush string and vibrant horn arrangements.